“РУСТАМХОН”ДОСТОНИДАГИ СИФАТ СЎЗ ТУРКУМИГА ХОС ЛЕКСЕМАЛАРНИНГ МЕТАФОРАЛАШУВИ - Ҳамдамова, Х. (SCIENCE and SOCIETY, 2022)
The article explores the methodological possibilities of lexemes in the text of the epic "Rustamkhan". The general similarities in the text of qualitative linguistic metaphors, as well as the epic skill and individuality of the bakhshi in this regard, are analyzed in the linguistic means that determine their specific style.